Automated Allergen Sample Preparation and Detection via Centrifugal Microfluidic Lateral Flow Assay - Bastian Breiner; Daniel M. Kainz; Stefan Wagner; Maxime Gavage; Serhat Sahakalkan; Riccardo Marega; Felix von Stetten; Anna Klebes (Proceedings)
Food allergies are a severe burden for affected individuals and healthcare systems. To tackle the need for simple food allergen detection, we developed a system for the detection of the soy protein glycinin via a centrifugal microfluidics-assisted lateral flow immunoassay (LFIA). Glycinin is a complex allergen requiring extensive sample preparation. The presented workflow includes a manual denaturing extraction, followed by automated centrifugal microfluidic desalting, metering and detection via LFIA. The functionality of the microfluidic cassettes was tested on prototypes produced via microthermoforming before an injection molding tool was designed, which added a cylindrical lens to improve the readout. Overall, this system aims to aid in food allergen detection with high sensitivity and minimized manual steps.